Sub-ex: Development of an autonomous underwater vehicle (phases I and II) - Alcaraz, Joseph Paulo P. (Animo Repository, 2009)
This project focuses on the two development stages of SUB-EX, an Autonomous Underwater Vehicle (AUV):1 (1) the AW platform and (2) the visual surveying control of software. As an AUV, SUB-EX can move in any horizontal direction, submerge and surface without water leakage and hover underwater. The visual surveying software allows the AUV to operate in manual or automatic mode. In manual operation, movements of the submarine are executed using a remote control. If automatic, the submarine uses color recognition and object tracking. Color recognition aids the submarine to identify a specific color, while object tracking allows it to automatically move towards an object in response to its recognized color. The system was tested in a swimming pool to better observe the AUV movements.